Synthesis of some 2-amino-4,6-diarylpyrimidine derivatives using microwave-assisted method - Thanh, Nguyen Dinh; Thanh Mai, Nguyen Thi; Nhan, Nguyen Phuong (Vietnam Journal of Chemistry, 2014)
Some new compounds of 2-amino-4,6-diarylpyrimidines have been synthesized from corresponding substituted chalcones and guanidine hydrochloride using two different synthetic methods in microwave oven. The products formed were equally available and confirmed by IR, 1H-NMR and mass spectral data.